Agammaglobulinemia and Staphylococcus aureus Botryomycosis in a Cohort of Related Sentinel Swiss Webster Mice - Bridgeford, Erin C. (American Society for Microbiology (ASM), 2008)
Sentinel mouse seroconversion to infectious agents is critical for laboratory animal facility disease monitoring. We report spontaneous emergence of non-sex-linked agammaglobulinemia with B-cell deficiency and cutaneous Staphylococcus aureus granulomatosis (botryomycosis) in a cohort of related Swiss Webster sentinel mice. Our experience reinforces the importance of immunocompetency validation in surveillance programs.